Collective Behavior Bees for Solving HW/SW Partitioning and Scheduling Problems in RSoC - Khadidja, Yahyaoui; Mohammed, Bouchoicha (Transactions on Engineering and Computing Sciences, 2017)
In the codesigndomain, many hardware and software techniques must bedeveloped to satisfyspecificconstraints in terms of computation time, area, performance, power consumption, etc.This paperintroduces an automaticapproachTo perform HW/SW partitioning and scheduling such that the global application execution time is minimized and the majority area of FPGA ( Field programmable gate array) used in RSoC ( Reconfigurable System on Chip) is exploited. The usedalgorithmisinspiredby the collective behavior of social insectssuch as bees. : Honey Bees Mating Optimization (HBMO). Comparing the proposed method with Genetic algorithm, the simulation results show that the proposed algorithm has better convergence performance.